An Innovative Extension Model for Integrated Rural Development: A Case of Samaj Shilpi Dampati Scheme - B. L. Manjunatha , D. U. M. Rao and Rashmi Singh (Indian Journal of Extension Education, 2016)
The research study conducted in Chitrakoot district of Uttar Pradesh state in India was aimed to study the philosophy,origin, process and functioning of the Samaj Shilpi Dampatis (SSD) scheme along with its socio-economic impact onlivelihood of the villagers. SSDs live in a village and work for a cluster of five villages. This cluster of five villages iscalled a SSD unit. One village was selected randomly from each SSD unit. Twenty farmer households were selectedrandomly from each village. Totally, 100 farm households were interviewed for primary data collection. Five SSDs (10functionaries) and twenty officials working in various organizations of DRI were also selected for primary data collection.The study found that SSDs, the grassroots level functionaries, possessed a very high level of achievement motivation,organizational commitment, dedication, faith in people, empowerment, and development orientation. The scheme had agreat impact on beneficiaries in their raise in income, savings, and increase in employment days. Majority of therespondents, especially marginal and small farmers, adopted either 1.5 or 2.5 acre model that helped ensure food securityfor their families throughout the year. Adoption of kitchen gardens in their homesteads helped secure nutritional securityfor the family. The village sanitation, health and hygiene of respondent households had improved a lot. More than 85 percent of the families shifted from below poverty line category to above poverty line category. The SSD scheme was foundto be cost-effective, efficient and worked for the integrated development of villages. This indigenous concept of ruraldevelopment needs to be considered for upscaling in other parts of the country. The model holds a great hope forgovernment departments, NGOs and voluntary organizations working at grassroots level.